2009
DOI: 10.1007/s00023-009-0400-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time-Dependent Coupling on Non-Equilibrium Steady States

Abstract: 30 pagesInternational audienceConsider (for simplicity) two one-dimensional semi-infinite leads coupled to a quantum well via time dependent point interactions. In the remote past the system is decoupled, and each of its components is at thermal equilibrium. In the remote future the system is fully coupled. We define and compute the non equilibrium steady state (NESS) generated by this evolution. We show that when restricted to the subspace of absolute continuity of the fully coupled system, the state does not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…In that case, the NESS only depends on the initial states of the reservoirs and on the final one-particle Hamiltonian. It is, in particular, independent of the initial state of the sample and of the (possibly time-dependent) switching of the coupling/bias [CNZ,CMP2]. In fact, the presence of eigenvalues in the one-particle Hamiltonian of the fully coupled/biased system produces oscillations which prevent relaxation to a steady state [Ste, KKSG].…”
Section: Introductionmentioning
confidence: 99%
“…In that case, the NESS only depends on the initial states of the reservoirs and on the final one-particle Hamiltonian. It is, in particular, independent of the initial state of the sample and of the (possibly time-dependent) switching of the coupling/bias [CNZ,CMP2]. In fact, the presence of eigenvalues in the one-particle Hamiltonian of the fully coupled/biased system produces oscillations which prevent relaxation to a steady state [Ste, KKSG].…”
Section: Introductionmentioning
confidence: 99%
“…It was Landauer and Büttiker who found that this current is directly related to the transmission coefficients of some natural scattering system related to this particle transport problem. The phenomenological approach of Landauer and Büttiker later has been justified in several papers by deriving the formula from fundamental concepts of the Quantum Mechanics, see the series of papers [1,5,8,9,10,11,12,13,14] and [19].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) If S = {H, H 0 } is time reversible and mirror symmetric we get from Lemma 2.14(ii) that σ ph nαm α ′ (λ) = σ ph n α ′ mα (λ), λ ∈ R, n, m ∈ N 0 , α, α ′ ∈ {l, r}, α = α ′ . Using that we get from (5.13) that (n)f (λ − µ − nω) − ρ ph (m)f (λ − µ − mω)) σ ph n α ′ mα (λ)dλ.Interchanging m and n we get(m)f (λ − µ − mω) − ρ ph (n)f (λ − µ − nω)) σ ph m α ′ nα (λ)dλ.Using that S is time reversible symmetric we get from Lemma 2 14. (i) that (m)f (λ − µ − mω) − ρ ph (n)f (λ − µ − nω)) σ ph nαm α ′ (λ)dλ.…”
mentioning
confidence: 99%
“…Then one expects the joint system S + R 1 + · · · to relax towards a non-equilibrium steady states (NESS). Such states have been constructed in [Ru1,AH,JP2,APi,OM,MMS,CDNP,CNZ]. They carry currents, have non vanishing entropy production rate,.…”
Section: Introductionmentioning
confidence: 99%